Pengaruh Lama Penyajian dan Konsentrasi Madu terhadap Kadar Vitamin C Minuman Air Jeruk Nipis (Citrus aurantifolia S.) - Pusparani Nur, Nathania; Mayun Permana, I Dewa Gde; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Lime is a fruit that contains high vitamin C. Holding time could decreased the vitamin C, and to prevent that, the addition of honey is needed. The aim of this study is to determine the effect of holding time and honey concentration on vitamin C content, and to determine the holding time and honey concentration that can produce the lime water beverage with the best characteristics. This study used a completely randomized block design with 2 factors, which are holding time with 3 levels of treatment 0, 30, and 60 minutes, and honey concentration with 3 levels of treatment 0, 5 and 10%. All treatments were combined and repeated 3 times to obtain 27 experimental units. The data was analysed by analysis of variance and the treatment that had a significant effect on the parameters was continued with DMRT. The results showed that the interaction of both factors had a significant effect on vitamin C, antioxidant activity, reducing sugar and total acid. Holding time caused decreased in vitamin C, antioxidant activity, total acid, reducing sugar, hedonic and scoring of taste. Whereas, honey concentration caused increased in all parameters except total acid that experience a degradation. Lime water beverage with the best characteristic is the lime water beverage with 30 minutes of holding time and 10% of honey concentration with the characteristics of vitamin C 1112.95 mg/100g, antioxidant activity 86.57%, reducing sugar 4.93%, total acid 1.97%, sweet taste, yellow brownish colour, taste was liked and colour was liked. Keywords: lime, honey, holding time, vitamin c, reducing sugar